Research on Aircraft Attitude Control Method Based on Linear Active Disturbance Rejection - Zhiguo Song; Changjian Zhao; Huiqiang Zhang; Tian Dong; Aojia Ma; Dawei Yan (International Journal of Aerospace Engineering)
In this paper, a dual-loop active disturbance rejection attitude controller design method is proposed for the attitude control of aircraft. Firstly, based on the nonlinear dynamic model of aircraft, the control system model with inner loop as angular velocity and outer loop as attitude angle is established. Secondly, the extended state observer for the inner loop is established to estimate and compensate the state of the system in real time. The controller of the compensated series integral system is designed by using the linear PD control method. Thirdly, the extended state observer and controller for the outer loop are designed by the same method. Finally, the stability proof of the dual-loop attitude control method is given based on the Lyapunov theorem of stability. Simulation results show that compared with the traditional PID attitude control method, the dual-loop ADRC attitude control method has better control quality in tracking speed, tracking error, and system anti-interference ability. The control parameters to be adjusted in this method have distinct physical significance. So this method has a wide range of engineering application prospects.